(untitled) (Birat Journal of Health Sciences, 2025)
Introduction: Poisoning is a leading cause of emergency department visits and hospital admissions worldwide. In Nepal, poisoning-related mortality is rapidly increasing, posing a significant public health challenge. Objectives: This study aims to evaluate the clinico-demographic profile, assess triage parameters at presentation, and determine their utility in predicting the outcomes of acute poisoning cases at a tertiary care hospital in Nepal. Methodology: All patients presenting to the emergency department with acute poisoning during the study period were enrolled. Data on demographics, clinical features, triage parameters, poison types, intubation requirement and outcomes were collected using a semi-standardized proforma. Primary outcomes were survival and mortality; secondary outcomes included admission details and complications. Results: A total of 1,003 patients were evaluated, with a female-to-male ratio of 1.7:1. The predominant age group was 20–30 years. Suicidal intent accounted for 92.2% of cases. The average time from poisoning to hospital arrival was 5.07 ± 4.08 hours. Organophosphates were the most common poisons. Intubation was required in 9% of cases. Complications occurred in 17.5%, and overall mortality was 6.3%. Abnormal respiratory rate (RR), oxygen saturation (SpO₂), and Glasgow Coma Scale (GCS) scores correlated strongly with poor outcomes. Conclusion: Acute poisoning primarily involves agricultural chemicals, Young adults with home-makers and students comprising most cases, with suicidal attempts at home presenting mainly with gastrointestinal symptoms. Abnormal triage vital signs are significant predictors of poor clinical outcomes.